2003
DOI: 10.1046/j.1440-6055.2003.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological studies of the Australian predatory mite Typhlodromips montdorensis (Schicha) (Acari: Phytoseiidae), a potential biocontrol agent for western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae)

Abstract: The biology of the Australian phytoseiid mite Typhlodromips montdorensis is described from material collected in Queensland and South Australia in 1994−1996. At 25°C, when fed on cumbungi (Typha sp.) pollen, the life cycle was completed in approximately 7 days, with an intrinsic rate of natural increase (rm) of 0.32. Female−male pairs produced a mean total of 52.7 eggs within 28 days of oviposition. Females that were deprived of males after first mating stopped laying eggs after 7−19 days; however, if another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
0
26
0
11
Order By: Relevance
“…The efficiency of natural enemies in a pest management program often varies from species to species (Chyzik et al, 1996;Berndt et al, 2004a,b), and several factors seem to be responsible. Similarly, T. montdorensis feeds on first instar F. occidentalis (Steiner et al, 2003). Bakker & Sabelis (1989) reported that N. cucumeris is able to predate on only the smallest thrips, which effectively limits them to attacking first instars of F. occidentalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of natural enemies in a pest management program often varies from species to species (Chyzik et al, 1996;Berndt et al, 2004a,b), and several factors seem to be responsible. Similarly, T. montdorensis feeds on first instar F. occidentalis (Steiner et al, 2003). Bakker & Sabelis (1989) reported that N. cucumeris is able to predate on only the smallest thrips, which effectively limits them to attacking first instars of F. occidentalis.…”
Section: Discussionmentioning
confidence: 99%
“…The other mite species tested, H. miles, inhabits the top soil layer (at about 1.3 cm depth) and preys only on F. occidentalis pupae (Glockemann, 1992), although some studies suggest that this mite also preys on late second instars (Berndt, 2003). Neoseiulus cucumeris is reported to feed on an average of six F. occidentalis larvae (first instar) per day (Zilahl-Balogh et al, 2007), while egg-laying female T. montdorensis feeds on 7-14 larvae per day (Steiner et al, 2003). Similarly, Brødsgaard (1989) and van Houten et al (1995) reported that N. cucumeris consumed higher numbers of F. occidentalis larvae compared with Amblyseius barkeri (Swirskii).…”
Section: Discussionmentioning
confidence: 99%
“…Native anthocorid predatory bugs do not appear to have a major impact on the pest (Cook et al 1996), but predatory mites seem to hold greater promise (Steiner et al 2003), and the possibility of adding an alarm pheromone to insecticides has also been examined (Cook et al 2002). Although glasshouse crops were the initial target, field crops are being increasingly attacked.…”
Section: Immigrant and Pest Thripsmentioning
confidence: 99%
“…Blackwood et al (2001) avaliaram a preferência para alimentação de 13 espécies de ácaros predadores, por ovos e larvas de T. urticae, concluindo que os ácaros mais especialistas preferiram alimentar-se de ovos, enquanto que os generalistas preferiram as larvas. Por outro lado, Steiner et al (2003) verifi caram que Typhlodromips montdorensis (Schicha) consumiu indiscriminadamente ovos e estágios pós-embrionários de T. putrescentiae.…”
Section: Discussionunclassified